Uma abordagem fonológica da segmentação na escrita de alunos do ensino fundamental II - Brandão, Maria Hellen (2015)
In this work, we present a study about unconventional segmentations such as hyposegmentation, hypersegmentation and hybrid segmentation in texts written by 7th year students from the Elementary School II. Structures like \'denovo\', \'subi solo\' and \'derre pente\' replacing \"de novo\", \"subsolo\" and \"de repente\", respectively, characterize these phenomena. From data extrated of a corpus constituted by 640 texts, written in the classroom, we made a description and a general analysis of the structures segmented in a non conventional way, in order to understand why students of this level of education are still segmenting words unconventionally. We aim, with the understanding of these phenomena, to make available to teachers from elementary school information on the functioning of the language, specifically, about phonological processes which may promote non conventional segmentations, along with a didactic proposal that deals with these phenomena. Among the theoretical discussions that subsidized us, are the proposal made by Bisol (1999) for the syllable treatment in brazilian portuguese; the Hayes\' (1995) proposal on the stress use and the Bisol\'s approach (1999,2005), grounded on Nespor and Vogel (1986), on the prosodic hierarchy. We also used studies done by Cunha (2004), Tenani (2011) and Silva (2014) on non conventional segmentations. The results of this work revealed a significant number of hyposegmentation cases: 67.2 percent of total data, contrasting with 32.3 percent of hypersegmentation cases and 0.5 percent of hybrid segmentation, which represent only two cases. Based on the descriptions and analysis made, it was evident that most hyposegmented and hypersegmented structures involves a grammatical word a clitic. From this result, we infer that the difficulty of the investigated population on segmenting is related to the use of clitic elements. Because of this, we purposed the activities that compose the didactic proposal, seeking to emphasize the appropriate segmantation of this kind of word, through the use of blank space and hyphen. About the second graphic sign referred, we aimed to instruct its use only to separate sequences formed by verb + pronoun in enclitic position